Matices del arte como orígenes de los objetos de diseño masivo en la sociedad de consumo - Vázquez Rodríguez, Gerardo (UNIVERSIDAD DE SONORA, 2022)
Our contemporary society at a global level is based on the establishment of a cultural, economic and production model that is sustained from the exacerbated phenomenon of consumption, giving shape to what we understand as a Consumer Society. This phenomenon had its beginnings at the same time as industrialization throughout the world, but its formulas and models for accessing the generalized population of the world are undoubtedly reflected in the mass production and consumption of design objects. In this document we propose to reflect from a theoretical apparatus such as what, from the teachings and sensitivity that art proposes in the observer, the objects of massive design were nuanced to generate the great contemporary dominance with which they now have over society and its habitual behaviors.